Metabolic activity of visceral adipose tissue is associated with age-related macular degeneration: a pilot 18F-FDG PET/CT study - Choi, Kwang-Eon; Joung, Chanmin; Pahk, Ki Joo; Kim, Hyunji; Pahk, Kisoo (Frontiers in Endocrinology, 2024)
Background Obesity is known to increase the risk and severity of age-related macular degeneration (AMD). Increased inflamed metabolic activity of visceral adipose tissue (VAT) is considered as a crucial underlying mechanism for the harmful effects of obesity. In this study, we aimed to investigate the inflamed metabolic activity of VAT with 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) and their association with AMD. Materials and methods A total of 57 elderly participants (aged ≥ 50 years) who underwent 18F-FDG PET/CT for health screening and subsequent fundoscopic exam for complaint of recently impaired vision were enrolled. The metabolic activity of VAT was measured from the maximum standardized uptake value (SUVmax) of VAT. The early AMD participant was defined as the participant with either eye satisfying AMD and without any sign of advanced AMD (neovascular AMD or geographic atrophy). The late AMD participant was defined as the participant with either eye satisfying advanced AMD. Results VAT SUVmax was highest in participants with late AMD, intermediate in early AMD, and lowest in non-AMD participants. The levels of systemic inflammation surrogate markers were also highest in late AMD group. Furthermore, VAT SUVmax was positively correlated with systemic inflammation surrogate markers and independently associated with the late AMD. Conclusions The metabolic activity of VAT evaluated by 18F-FDG PET/CT was associated with the severity of AMD and synchronized with the level of systemic inflammation. Thus, VAT SUVmax could be potentially employed as a surrogate marker of obesity-driven VAT inflammation associated with AMD.